Dominant optic atrophy in Denmark - report of 15 novel mutations in OPA1, using a strategy with a detection rate of 90% - Almind Gitte J; Ek Jakob; Rosenberg Thomas; Eiberg Hans; Larsen Michael; LuCamp LuCamp; Brøndum-Nielsen Karen; Grønskov Karen (BMC, 2012)
Abstract Background Investigation of the OPA1 mutation spectrum in autosomal dominant optic atrophy (ADOA) in Denmark. Methods Index patients from 93 unrelated ADOA families were assessed for a common Danish founder mutation (c.2826_2836delinsGGATGCTCCA) inOPA1. If negative, direct DNA sequencing of the coding sequence and multiplex ligation-dependent probe amplification (MLPA) were performed. Results from MLPA analysis have been previously reported. Haplotype analysis was carried out analysing single nucleotide polymorphisms (SNP). Retrospective clinical data were retrieved from medical files. Results Probably causative mutations were identified in 84 out of 93 families (90%) including 15 novel mutations. Three mutations c.983A > G, c.2708_2711delTTAG and c.2826_2836delinsGGATGCTCCA, were responsible for ADOA in10, 11 and 28 families, respectively, corresponding to 11%, 12% and 30%. A common haplotype in nine of ten c.983A > G families suggests that they descend from a single founder. The c.2708_2711delTTAG mutation was present on at least two haplotypes and has been repeatedly reported in various ethnic groups,thus represents a mutational hotspot. Clinical examinations of index patients with the two latter mutations demonstrated large inter- and intra-familial variations apparently. Conclusions Genetic testing for OPA1mutations assist in the diagnosis. We have identified mutations in OPA1 in 90% of families including 15 novel mutations. Both DNA sequencing and MLPA analysis are necessary to achieve a high detection rate. More than half of the affected families in Denmark are represented by three common mutations, at least two of which are due to a founder effect, which may account for the high prevalence of ADOA in Denmark.